2020
DOI: 10.1042/bst20200239
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy protein theory for disordered proteins

Abstract: Why proteins are fuzzy? Constant adaptation to the cellular environment requires a wide range of changes in protein structure and interactions. Conformational ensembles of disordered proteins in particular exhibit large shifts to activate or inhibit alternative pathways. Fuzziness is critical for liquid–liquid phase separation and conversion of biomolecular condensates into fibrils. Interpretation of these phenomena presents a challenge for the classical structure-function paradigm. Here I discuss a multi-valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…For the (GSK) n -GFP x systems, we found that tail length and the size/charge of an adjoining patch can provide complementary properties that influence conformational behavior. As a more general model, interactions between polyelectrolytic tails and electrostatically complementary adjoining patches are dictated by a complex balance between energetically favorable IDR-FD interactions vs. unfavorable IDR-IDR interactions, and the conformational entropic cost of interacting with a specific region on the surface ( i.e., the entropic cost of “fuzzy” binding) ( Tompa and Fuxreiter, 2008 ; Arbesú et al., 2018 ; Fuxreiter, 2020 ). An additional feature not well captured in our work is the energetically (entropically) favorable contribution of ion release that conventionally is considered to drive complex coacervation ( Sing and Perry, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the (GSK) n -GFP x systems, we found that tail length and the size/charge of an adjoining patch can provide complementary properties that influence conformational behavior. As a more general model, interactions between polyelectrolytic tails and electrostatically complementary adjoining patches are dictated by a complex balance between energetically favorable IDR-FD interactions vs. unfavorable IDR-IDR interactions, and the conformational entropic cost of interacting with a specific region on the surface ( i.e., the entropic cost of “fuzzy” binding) ( Tompa and Fuxreiter, 2008 ; Arbesú et al., 2018 ; Fuxreiter, 2020 ). An additional feature not well captured in our work is the energetically (entropically) favorable contribution of ion release that conventionally is considered to drive complex coacervation ( Sing and Perry, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, protein regions that drive aggregation within liquid-like condensates are capable of switching between disordered and ordered interactions ( 23 ). This interaction property, which changes between interaction modes, is denoted as context-dependence, which leads to a wide variety of cellular behaviors under different conditions ( 35 , 36 ).…”
Section: Principles To Enable the Prediction Of The Condensed State B...mentioning
confidence: 99%
“…Especially in situations in which proteins or protein complexes are required to respond to changing cellular conditions by scanning large ensembles of different RNA molecules ( 56 ). As such, our finding represents a logical extension of the fuzzy protein theory for disordered proteins ( 69 , 70 ) by merging the fuzziness and frustration concepts in the energy landscape of proteins with that of RNA molecules ( 71 ). As much as frustration in fuzzy protein/protein complexes causes a multiplicity of specific interactions ( 72 , 73 ), it is conceivable that frustration in RNA/protein complexes is responsible for the observed nonbinary pre-mRNA-binding characteristics of the T. brucei editosome.…”
Section: Discussionmentioning
confidence: 79%